Kontribusi Tokoh Punakawan pada Pagelaran Wayang Kulit terhadap Pendidikan Islam kepada Masyarakat - Eddy Saputra (Universitas Indraprasta PGRI Jakarta, 2021)
Wayang as the only entertainment for the people is used as a media approach to convey Islamic teaching values. This is adopted by Sunan Kalijaga as a media approach. By including a new character which is The Punakawan in the middle of a popular character previously, Pandawa Lima, even though it is not in the original story. Wayang is so attached to Javanese culture and tradition although that story is taken from India. The punakawan figure becomes a differentiator in the wayang kulit story that is carried out with the Javanese punakawan's distinctive name having a prerequisite meaning with Islamic values. Punakawan also teaches moderation in religion that does not intersect with local culture. This study uses a literature study approach, data collected through books, notes, historical stories and others. Islamic education always puts forward a moral and moral approach, from this aspect, the Punakawan figures are raised. The Javanese people believe that the existence of Punakawan figures seems to have lived in the real world, for example Mount Tidar in Cilalap Regency is believed to be the place where Semar lives.